PARASITES AND PREDATORS OF CLETUS SIGNATUS WALKER (HETEROPTERA : COREIDAE) - AGARWAL, B. L.; DHIMAN, S. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
Cletus signatus infests a wide range of host plants in north-western U.P. One ectoparasite, Leptus sp , and two predators, r reying mantid (Hierodula sp.) and Araneus sp. of spider are observed as natural enemies of this bug. Adults and nymphal instars with a load of 5 to 15 mite larvae become quite sluggish, die later on,